Effect of Argument Driven Inquiry (ADI) with Problem Solving Method for Student’s Argumentation and Critical Thinking Skills - Fatmawati, Zulfa Ayuningtyas; Mulyani Endang Susilowati, Sri; Sri Iswari, Retno (Journal of Innovative Science Education, 2019)
Problem solving skill is needed by the students on the daily basis; therefore, the innovation is demanded in the learning process. ADI model with problem solving method is the learning innovation which is expected to improve the students' thinking skills and giving the argument. This research aims to describe the effect of ADI model with problem solving method on the argumentation and critical thinking skills. This research was the experimental study employing cluster random sampling technique. The data analysis technique used independent sample t-test. The result of the students' pretest shows that the students’ argumentation and critical thinking skills are in the poor category. Meanwhile, the result of the posttest shows that the there is the improvement on the students’ skills after being given the treatment in the form of ADI model with Problem Solving method. Based on the result of the analysis, it can be concluded that the implementation of ADI model with Problem Solving method has the effect on the argumentation and critical thinking skills. Viewed from the result of t-test from n-gain result, experimental class is higher than the control class. The learning activity that applies this method will be developed if the teachers can design the contextual activities and provide the questions related to the students’ real life in which they are not merely stated in the textbook. Problem-solving skills are needed by students in everyday life, So it needs an innovation in the learning activities in school. Argument Driven Inquiry (ADI) models with Problem Solving method is a learning innovation that is expected to improve students' ability to think and argue. The purpose of this research is to describe the influence of Argument Driven Inquiry (ADI) model of Problem Solving to the ability of argumentation and critical thinking. This study was an experimental study with the entire population of students of class VIII SMP Muhammadiyah 3 Semarang. Sampling using probability sampling and cluster random sampling. Class VIII G as an experimental class treated Argument Driven Inquiry (ADI) models with Problem Solving Method and VIII F as a control class that are subjected to information and discussion models. Data in the form are argumentation skills and critical thinking skills. Data were analyzed using independent sample t test.  The results of pretest show that students' argumentation and critical thinking are in the low category. While posttest result indicate that there is improvement of student ability after given treatment ADI with problem solving method. Based on the results of data analysis can be concluded that the application of the model ADI with Problem Solving method affect the development of argumentation and critical thinking skills. Viewed of n-gain t test experiment class ability is higher than the control class. This Learning activities can be developed better by teachers with designing learning activities contextually and give questions related to student life, not just about textbooks.